Karya Roh Kudus Dalam Pendidikan Kristen, Analisis Teks Kisah Para Rasul 2:42 Dan Relevansinya Bagi Pendidikan Kristen Masa Kini - Sularno, Misael; Usmany, Janneman; Hamzah, Amir (DIDAKTIKOS: Jurnal Pendidikan Agama Kristen, 2023)
Often people limit the work of the Holy Spirit to things related to spiritual gifts. Apart from spectacular things like healing the sick or raising the dead, prophesying about what will happen, speaking in tongues, is not considered the work of the Holy Spirit. This paper describes the work of the Holy Spirit which is realized in four important church activities recorded in Acts 2:42. These four activities are the tasks of the church initiated by the Holy Spirit, namely the teaching of the apostles (didache), communion (koinonia), breaking of bread (diakonia), and praying (proseuche). The current condition of the church demands an active role from its leaders to return to work on these four things so that the church today does not lose its identity as a community of believers who make disciples of all nations of Christ.